The Influence of Using Pop Up Book Media on the Early Reading Skills of Children with Mental Disabilities - Wardah, Dinah Nur; Rejeki, Dewi Sri; Martika, Tias (Department of Special Education, 2023)
This research aims to know the influence of pop up book toward early reading ability of intellectual disability children of class IV C SLB Negeri Purbalingga in academic year of 2022/2023. This research used quantitative method. The design of this research is experiment one group pretest-posttest design. Subject of this research are 5 children with intellectual disability of class IV C SLB Negeri Purbalingga in the Academic Year of 2022/2023. The data collection technique is a reading test that have been tested for validity and reliability with content validity and reliability Interclass Correlation Coefficients (ICC). The data analysis techniaque in this sresearch used the Wilcoxon Sign Rank. The result show that the Asymp. Sig (2-tailed) scores at 0,43. The result of this research was significant to prove the effectiveness of the pop up book to increase early reading ability of intellectual disability children of class IV C SLB Negeri Purbalingga in academic year of 2022/2023.